High-temperature pavement crack pouring adhesive and preparation method thereof

By using the combination of premixing, polymer modifiers, adhesives, stabilizers and fillers in the irrigation glue, and using the prefabrication method of rubber modified asphalt premixing, solve the existing heating -type irrigation seam The tedious and high construction viscosity of the glue achieves the high temperature stability and low temperature performance of the sewing glue, and reduces the preparation cost.

CN119351053AActive Publication Date: 2025-01-24浙江顺畅高等级公路养护有限公司 +1

Patent Information

Application Number
CN202411665308.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-01-24
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

The existing heating-type seam filling glue is complicated in the processing of polymer modified asphalt, with high construction viscosity, poor environmental suitability, and high preparation cost.

Method used

The combination of premixing, polymer modifiers, adhesives, stabilizers and fillers can reduce the prefabrication of rubber modified asphalt premix to reduce the preparation time of the later sewing gum, and improve the asphalt of the rubber powder and matrix. Uniformity and quality stability.

Benefits of technology

The high temperature and stability performance, low temperature performance, and elastic recovery performance of sewing gum are realized. It has a lower high temperature viscosity, convenient construction and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119351053A_ABST
    Figure CN119351053A_ABST
Patent Text Reader

Abstract

The invention provides a high-temperature pavement crack pouring adhesive and a preparation method thereof, and relates to the technical field of pavement maintenance, the high-temperature pavement crack pouring adhesive comprises the following components: a premix, a polymer modifier, a tackifier, a stabilizer and a filler; and the filler contains a finely separated recycled material. The high-temperature pavement crack pouring adhesive has the characteristics of high temperature and high resilience by adding the rubber modified asphalt, the low-temperature performance is improved by adding the polymer modifier, the viscosity, toughness and durability are ensured by adding the tackifier, the stability and aging resistance are ensured by adding the stabilizer, all the materials play a synergistic effect, the comprehensive performance of the crack pouring adhesive is balanced, and the service life of the crack pouring adhesive is prolonged. According to the present invention, by adding the fine separation reclaimed material, the crack pouring adhesive has characteristics of good high temperature stability, low temperature performance balance, elastic recovery performance balance, environmental adaptability, low high temperature viscosity, balanced performance, convenient construction and low cost, and the simple and efficient regeneration utilization of the fine separation reclaimed material is achieved by adding the fine separation reclaimed material, the problem that the recycling rate of fine separation recycled materials is low is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of pavement maintenance, and in particular to a high-temperature pavement joint sealing adhesive and a preparation method thereof. Background Art

[0002] Common caulking materials are divided into cold caulking, hot caulking and chemical materials. Among them, hot caulking asphalt caulking glue has the advantages of good adhesion to old pavement, low cost and mature application. It is currently a commonly used highway maintenance material for asphalt pavement crack repair and cement pavement filling. However, there are still widespread problems of uneven performance and poor application effect. In order to meet the actual service environment requirements of long-term vehicle-mounted, water and high temperature, the caulking glue must have performance characteristics such as good water sealing, strong adhesion to old pavement, and good aging resistance. At the same time, in order to meet the convenience of caulking construction, the caulking glue must have a lower viscosity at high temperature. The technical defects of existing heated caulking glues are mainly reflected in technical problems such as cumbersome processing of polymer-modified asphalt, high construction viscosity, and poor environmental applicability.

[0003] CN201210262849.7 proposes an asphalt high-temperature pavement crack sealant and a preparation method thereof, wherein the crack sealant is composed of a compatibilizer, a modifier, a stabilizer and a matrix asphalt, wherein the compatibilizer is a second-line extraction oil, a third-line extraction oil or a mixture thereof with a high aromatic content, and for the third-line extraction oil, its preparation involves many processes, and the oil output needs to meet certain standards, which increases the preparation cost, and during the preparation process, the compatibilizer needs to be preheated to 40-60°C and then blended with the matrix asphalt, and the preparation steps are relatively cumbersome. Although the crack sealant has certain high and low temperature performance and deformation recovery ability, its molecular polarity is low, and the long-term bonding and repair effect on pavement cracks is not ideal.

[0004] CN202010487751.6 uses matrix asphalt, silica resin, tackifying resin and additives to prepare a caulking glue. The caulking glue obtained by this preparation method has a flow value greater than 0 at 60°C. The caulking glue may be squeezed out of the cracks as the ambient temperature rises and be carried away by the tires of passing vehicles, thereby affecting the stability of the crack treatment and has limited applicability in high-temperature environments.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] One of the purposes of the present invention is to provide a high-temperature pavement caulking glue to at least solve one of the technical problems existing in the prior art. The high-temperature pavement caulking glue provided by the present invention comprises a premix, a polymer modifier, a tackifier, a stabilizer and a filler. Through the specific and synergistic effects of each component material, the caulking glue has good high-temperature stability and better comprehensive performance, making the caulking glue more environmentally adaptable.

[0007] The second purpose of the present invention is to provide a method for preparing a high-temperature pavement caulking glue. The method for preparing a high-temperature pavement caulking glue provided by the present invention first prepares a rubber-modified asphalt premix, and then adds other components for blending. The pre-preparation process of the premix reduces the preparation time of the later caulking glue, and at the same time enables the rubber powder and the matrix asphalt to fully blend with each other, thereby improving the uniformity and quality stability of the caulking glue.

[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0009] In a first aspect, the present invention provides a high-temperature pavement crack sealing adhesive, comprising the following components: a premix, a polymer modifier, a tackifier, a stabilizer and a filler;

[0010] Wherein, the premix includes rubber powder and base asphalt.

[0011] Furthermore, the high-temperature pavement sealant comprises the following components by mass percentage:

[0012] 65%-75% premix, 2%-4% polymer modifier, 0.5%-1.5% tackifier, 0.1%-0.5% stabilizer and 10%-32% filler;

[0013] The premix comprises the following components by mass percentage: 15%-25% rubber powder and 75%-85% base asphalt.

[0014] Further, the base asphalt includes 70# heavy cross-linked base asphalt;

[0015] The particle size of the rubber powder is 60-100 meshes, the ash value of the rubber powder is ≤18%, and the acetone extract content of the rubber powder is ≤20%.

[0016] Further, the filler includes at least one of finely separated recycled material and stone powder;

[0017] Preferably, the stone powder includes at least one of mineral powder and talcum powder;

[0018] Preferably, the particle size of the finely separated recycled material is ≤3 mm, the moisture content of the finely separated recycled material is ≤0.5%, the old asphalt content of the finely separated recycled material is 6%-8%, and the needle penetration of the old asphalt is ≥20 (0.1 mm);

[0019] Preferably, the particle size of the stone powder is ≤0.15 mm.

[0020] Furthermore, the polymer modifier includes at least one of linear T6302H, T161 and T171 styrene-butadiene-styrene block copolymers.

[0021] Furthermore, the tackifier includes at least one of C9 resin, C5 resin and EVA.

[0022] Furthermore, the stabilizer includes sulfur.

[0023] In a second aspect, the present invention provides a method for preparing the high-temperature pavement crack sealing adhesive, comprising the following steps:

[0024] The rubber powder and the base asphalt are mixed according to the formula amount to obtain a premix;

[0025] The premix, polymer modifier, tackifier, stabilizer and filler are mixed according to the formula amount to obtain the high-temperature pavement crack sealing glue.

[0026] Furthermore, the process of mixing the rubber powder and base asphalt includes: heating the base asphalt to 160°C-170°C, adding the rubber powder, stirring for 20-30 minutes to obtain mixture A, controlling the temperature of mixture A to 170-180°C, shearing for 20-40 minutes at a shear rate of 4000-6000r / min, and then stirring for 10-12 hours at a stirring rate of 1500-2000r / min to obtain a premix.

[0027] Furthermore, the pretreatment process of the finely separated recycled material includes: subjecting the asphalt mixture recycled material to dry fine separation treatment, and screening to obtain the finely separated recycled material;

[0028] The process of mixing the premix, polymer modifier, tackifier, stabilizer and filler comprises: controlling the temperature of the premix to 175°C-185°C, adding the polymer modifier, tackifier and fine separation recycled material, stirring for 30-60 minutes at a stirring rate of 600-1000 r / min, then shearing for 20-40 minutes at a shear rate of 4500-5000 r / min, then stirring for 2-4 hours to obtain a mixture B, maintaining the temperature of the mixture B at 175°C-185°C, adding the stabilizer, stirring for 1-2 hours at a stirring rate of 600-1000 r / min to obtain a mixture C, and when the filler also includes stone powder, maintaining the temperature of the mixture C at 175°C-185°C, adding other fillers, and then stirring for 1-2 hours at a stirring rate of 600-1000 r / min.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] The high-temperature pavement caulking glue provided by the present invention has the characteristics of high temperature and high resilience by adding rubber modified asphalt, improves the low-temperature performance by adding a polymer modifier, ensures the viscosity and durability by adding a viscosity enhancer, and ensures the stability and anti-aging properties by adding a stabilizer. Various materials play specific and synergistic roles to balance the comprehensive properties of the caulking glue, making the caulking glue more environmentally adaptable and having good high-temperature stability. At the same time, the low-temperature performance and elastic recovery performance are balanced and the caulking glue has lower high-temperature viscosity. The caulking glue has balanced performance, convenient construction and low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0032] Figure 1 A flow chart of a method for preparing pavement crack sealing glue provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0033] Unless otherwise defined herein, scientific and technical terms used in conjunction with the present invention shall have the meanings commonly understood by those of ordinary skill in the art. The meaning and scope of the terms should be clear, however, in the case of any potential ambiguity, the definitions provided herein take precedence over any dictionary or external definitions. In this application, unless otherwise stated, the use of "or" means "and / or". In addition, the use of the term "including" and other forms is non-limiting.

[0034] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] The first aspect of the present invention provides a high-temperature pavement crack sealing adhesive, comprising the following components: a premix, a polymer modifier, a tackifier, a stabilizer and a filler;

[0036] Wherein, the premix includes rubber powder and base asphalt.

[0037] The pavement caulking glue in the present invention is a high-temperature pavement caulking glue. The components of the high-temperature pavement caulking glue have the characteristics of high temperature and high resilience by adding rubber modified asphalt, improve the low-temperature performance by adding a polymer modifier, ensure the viscosity and durability by adding a viscosity enhancer, and ensure the stability and anti-aging properties by adding a stabilizer. Various materials play a specific and synergistic role, balance the comprehensive performance of the caulking glue, make the caulking glue more environmentally adaptable, and make the caulking glue have good high-temperature stability (softening point can reach >100°C), while balancing the low-temperature performance (0°C, 25%, 3 cycles passed) and elastic recovery performance (elastic recovery can reach >40%), and at the same time have a lower high-temperature viscosity (180°C Brookfield viscosity can reach <10Pa·s). The caulking glue has balanced performance, convenient construction and low cost.

[0038] In some preferred embodiments, the high-temperature pavement sealant comprises the following components by mass percentage:

[0039] 65%-75% premix, 2%-4% polymer modifier, 0.5%-1.5% tackifier, 0.1%-0.5% stabilizer and 10%-32% filler;

[0040] Taking the total mass of the high-temperature pavement sealant as 100%, the addition amount of the premix is ​​65%-75%, for example, it can be 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, etc.;

[0041] Taking the total mass of the high-temperature pavement sealant as 100%, the addition amount of the polymer modifier is 2%-4%, for example, 2%, 2.5%, 3%, 3.5%, 4%, etc.;

[0042] Taking the total mass of the high-temperature pavement joint sealant as 100%, the added amount of the tackifier is 0.5%-1.5%, for example, 0.5%, 1%, 1.5%, etc.;

[0043] Taking the total mass of the high-temperature pavement sealant as 100%, the amount of stabilizer added is 0.1%-0.5%, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, etc.;

[0044] Taking the total mass of the high-temperature pavement sealant as 100%, the added amount of the filler is 10%-32%, for example, it can be 10%, 15%, 20%, 25%, 30%, 32%, etc.;

[0045] The premix comprises the following components by mass percentage: 15%-25% rubber powder and 75%-85% base asphalt.

[0046] Taking the total mass of the premix as 100%, the amount of rubber powder added is 15%-25%, for example, it can be 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, etc.;

[0047] Taking the total mass of the premix as 100%, the addition amount of the base asphalt is 75%-85%, for example, it can be 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, etc.

[0048] In some preferred embodiments, the base asphalt includes 70# heavy crosslinked base asphalt;

[0049] In the present invention, the matrix asphalt is one of the main components of the caulking glue. As the main adhesive, it provides good water-sealing and bonding properties, and together with the polymer modifier and glue powder, improves the viscoelasticity and anti-aging ability of the caulking glue.

[0050] Preferably, the particle size of the rubber powder is 60-100 meshes, the ash value of the rubber powder is ≤18%, and the acetone extract content of the rubber powder is ≤20%.

[0051] In the present invention, the ash value is required to be ≤18%. This is because the actual effective rubber component in the rubber powder with a high ash value is reduced, which will weaken the modification effect; the acetone extract content is required to be ≤20%. A lower acetone extract content means that the soluble impurity content in the rubber powder is lower, ensuring the quality of the caulking glue. Rubber powder mainly comes from scrap tires of cars. Adding rubber powder to the caulking glue is a composite modification: after swelling and degradation in the matrix asphalt, the rubber powder can improve the high temperature stability and low temperature deformation characteristics of the caulking glue; the carbon-carbon bonds and carbon-sulfur bonds in the rubber will break and recombine at the high temperature of the caulking glue preparation to form a more stable molecular structure. This process helps to improve the durability and anti-aging properties of the modified caulking glue; the carbon black particles in the rubber powder are evenly distributed in the caulking glue, acting as fillers, increasing the density and viscosity of the caulking glue, reducing its fluidity and enhancing high temperature stability; in addition, the rubber powder plays a role of physical support in the caulking glue, forming a structure similar to a skeleton, which enhances the stability of the internal structure of the caulking glue; the presence of rubber powder can fill the micropores in the caulking glue, making the structure of the caulking glue tighter, and improving the water damage resistance and anti-aging properties of the caulking glue. The synergistic effect of rubber powder and SBS modifier can enhance the crack resistance and tensile strength of the caulking glue.

[0052] In some preferred embodiments, the filler includes at least one of finely separated recycled material and stone powder;

[0053] The pavement caulking glue in the present invention is a high-temperature pavement caulking glue containing finely separated recycled materials. RAP is a solid waste generated during the maintenance and repair of highway asphalt pavements. RAP consists of two parts, old mineral materials and old asphalt. The two parts are bonded together. It is a commonly used technical approach to reuse them on asphalt pavements after factory-mixed hot regeneration. Fine separation technology is a RAP pretreatment method, which can peel off the old asphalt and old mineral materials on RAP, and enrich the old asphalt on the coarse RAP on the fine RAP, so as to solve the problems of particle adhesion and difficulty in controlling the grading of mineral materials. The present invention makes full use of the old asphalt and old mineral materials in the finely separated recycled materials, supplements the asphalt and stone powder required for the caulking glue, reduces the amount of new materials used, reduces the cost of caulking glue materials, and at the same time gives play to the advantages of high softening point index of old asphalt and ground old mineral materials as fillers to reduce viscosity and increase elasticity. The present invention uses the old asphalt and old mineral materials in the finely separated recycled materials to provide the necessary raw materials for the caulking glue, and combines the improvement of the preparation method of the caulking glue, without increasing the processing cost, to solve the problems of the difficulty of recycling the finely separated fine-grade recycled materials and the low recycling rate caused by the secondary aging of the heating of the regeneration drum in the factory-mixed hot regeneration, the low amount of the recycled mixed materials and the unstable performance. The invention realizes the simple and efficient recycling of the finely separated recycled materials, and solves the problem of the low recycling rate of the finely separated recycled materials.

[0054] Preferably, the particle size of the finely separated recycled material is ≤3 mm, the moisture content of the finely separated recycled material is ≤0.5%, the old asphalt content of the finely separated recycled material is 6%-8%, and the needle penetration of the old asphalt (100 g, 25° C., 5 s) is ≥20 (0.1 mm);

[0055] In the present invention, the finely separated recycled material is processed by dry fine separation technology, and its maximum particle size does not exceed 3mm. On the one hand, this is because the old asphalt content in this part of the recycled material is the highest and the utilization value is higher. It is also to ensure that the smaller finely separated recycled material in the preparation method can enter the colloid mill, thereby ensuring the shear efficiency and shear effect. At the same time, the smaller particle size also provides a larger specific surface area, thereby ensuring that the old asphalt can fully contact with the premix and promote miscibility; the old asphalt content is required to be 6% to 8%. On the one hand, it is to ensure that there is a sufficient amount of old asphalt to reflect the utilization value. At the same time, the old asphalt content that is too high is to avoid its adverse effects on the matrix asphalt content or the performance of the caulking glue; the needle penetration is used to characterize the aging degree of the old asphalt, and the needle penetration of the old asphalt (100g, 25℃, 5s) is required to be ≥20 (0.1mm), which can ensure that the old asphalt in the finely separated recycled material has a certain flexibility and plasticity, and the matrix asphalt can be fully regenerated; the moisture content of the finely separated recycled material is ≤0.5%, in order to ensure the heating efficiency of the finely separated recycled material and the accurate material measurement. The finely separated recycled material plays the role of replacing stone powder and a part of the matrix asphalt. Under the preparation method of the present invention, under the action of high temperature, shearing and penetration of asphalt flocs, the old mineral material in the finely separated recycled material is sheared from a maximum particle size of 3mm to less than 0.075mm, and the old asphalt in the finely separated recycled material is mixed with the premix, wherein the large asphalt micelles are broken, exposing many active points, and these active points combine with small molecules in the asphalt to form semi-polymerization, which can form new asphalt colloids, thereby realizing the regeneration of the old asphalt in the finely separated recycled material.

[0056] Preferably, the stone powder includes at least one of mineral powder and talcum powder;

[0057] Preferably, the particle size of the stone powder is ≤0.15 mm.

[0058] In the present invention, the stone powder is stone powder processed from natural crushed stone, with a 0.075mm sieve hole pass rate of ≥90% and a 0.15mm sieve hole pass rate of 100%, and more preferably a mineral powder or talcum powder processed from limestone. Stone powder can enhance the adhesion between asphaltene and SBS and resin due to its uniform particle size and strong dispersibility, making it easier for the caulking glue to adhere to the cracks of the road and enhancing the bonding force. In addition, stone powder can improve the high-temperature fluidity of the caulking glue, making it easier to construct and apply, and facilitating the control of the construction fluidity and coverage area of ​​the caulking glue. Adding stone powder can reduce the temperature sensitivity of the caulking glue, because stone powder can be adsorbed on the surface of asphalt molecules to form a firm asphalt film, thereby improving the viscosity and durability of the caulking glue and ensuring good construction performance.

[0059] In some preferred embodiments, the polymer modifier includes at least one of linear T6302H, T161 and T171 styrene-butadiene-styrene (SBS) block copolymers.

[0060] In the present invention, the SBS modifier can improve the high and low temperature performance, anti-aging ability and durability of the caulking glue. The spatial network structure formed by SBS at high temperature absorbs the oil in the asphalt, expands the swelling volume, and the polymer is converted from a dispersed phase to a continuous phase. Under the action of external force stirring and shearing, it is mainly physically modified to improve the high and low temperature performance of the caulking glue. The SBS modifier works together with the rubber powder and the resin to enable the caulking glue to maintain stable performance under high and low temperature conditions, and balance the high and low temperature performance.

[0061] In some preferred embodiments, the tackifier includes at least one of C9 resin, C5 resin and EVA.

[0062] In the present invention, the resin is further preferably C9 resin or EVA, and the molecular weight is less than 2000. Resin is a by-product of petroleum cracking, and is a thermoplastic resin obtained by copolymerizing with aldehydes, aromatic hydrocarbons, etc. under the action of a catalyst. The main function of the resin is to increase the viscosity and toughness of the caulking glue, thereby improving the performance and service life of the caulking glue. The mechanism is that the resin reacts chemically with the oil in the asphalt to form a composite with viscosity and ductility; after the addition of the resin, the network structure of the SBS is enhanced, and the light components cracked after the swelling of the rubber powder are constrained to form more asphalt flocs, and interact with the flocs formed by the SBS, thereby improving the adhesion and durability of the caulking glue.

[0063] In some preferred embodiments, the stabilizer includes sulfur.

[0064] In the present invention, the main function of the stabilizer is to improve the stability of the caulking glue, prevent the caulking glue from being delaminated and segregated, and improve the anti-aging performance of the caulking glue. The main mechanism is that sulfur interacts with polar groups and non-polar groups in the matrix asphalt to form a stable spatial network structure, inhibit phase separation, and also trigger the cross-linking reaction of the SBS modifier to enhance the stability of the caulking glue.

[0065] A second aspect of the present invention provides a method for preparing a high-temperature pavement crack sealing adhesive, comprising the following steps:

[0066] The rubber powder and the base asphalt are mixed according to the formula amount to obtain a premix;

[0067] The premix, polymer modifier, tackifier, stabilizer and filler are mixed according to the formula amount to obtain the high-temperature pavement crack sealing glue.

[0068] In some preferred embodiments, the process of mixing the rubber powder and the base asphalt includes: heating the base asphalt to 160°C-170°C, adding the rubber powder, stirring for 20-30min, for example, 20min, 25min, 30min, etc., to obtain a mixture A, controlling the temperature of the mixture A to 170-180°C, for example, 170°C, 175°C, 180°C, etc., and shearing for 20-40min, for example, 20min, 25min, 30min, 35min, 40min n, the shear rate is 4000-6000r / min, for example, 4000r / min, 5000r / min, 6000r / min, etc., and then stirred for 10-12h, for example, 10h, 11h, 12h, etc. The stirring rate is 1500-2000r / min, for example, 1500r / min, 1600r / min, 1700r / min, 1800r / min, 1900r / min, 2000r / min, etc. to obtain a premix.

[0069] In some preferred embodiments, the pretreatment process of finely separated recycled materials includes: subjecting recycled asphalt mixture (RAP) to dry fine separation treatment and screening to obtain finely separated recycled materials;

[0070] The process of mixing the premix, polymer modifier, tackifier, stabilizer and filler comprises: controlling the temperature of the premix to 175° C.-185° C., for example, 175° C., 180° C., 185° C., etc., adding the polymer modifier, tackifier and fine separation recycled material, stirring for 30-60 minutes, for example, 30 minutes, 40 minutes, 50 minutes, 60 minutes, etc., and stirring at a rate of 600-1000 r / min, for example, 600 r / min, 700 r / min, etc. 00r / min, 800r / min, 900r / min, 1000r / min, etc., and then shearing for 20-40min, such as 20min, 30min, 40min, etc., the shear rate is 4500-5000r / min, such as 4500r / min, 4600r / min, 4700r / min, 4800r / min, 4900r / min, 5000r / min, etc., and then stirring Stir for 2-4h, for example, 2h, 3h, 4h, etc., to obtain mixture B, maintain the temperature of mixture B at 175°C-185°C, for example, 175°C, 180°C, 185°C, etc., add stabilizer, stir for 1-2h, for example, 1h, 1.5h, 2h, etc., and the stirring rate is 600-1000r / min, for example, 600r / min, 700r / min, 800r / min, 900r / min, 1000r / min in, etc., to obtain a mixture C. When the filler also includes stone powder, the temperature of the mixture C is maintained at 175°C-185°C, for example, 175°C, 180°C, 185°C, etc., other fillers are added, and then stirred for 1-2h, for example, 1h, 1.5h, 2h, etc., and the stirring rate is 600-1000r / min, for example, 600r / min, 700r / min, 800r / min, 900r / min, 1000r / min, etc.

[0071] The method for preparing pavement caulking glue provided by the present invention provides raw materials with lower preparation cost for caulking glue. In addition, through raw material selection and formula optimization, the comprehensive road performance of traditional caulking glue is improved, thereby ensuring the application effect of asphalt pavement crack treatment or cement pavement filler.

[0072] Further, preferably, Figure 1 As shown, the preparation method of the pavement joint filling glue specifically includes the following steps:

[0073] (1) Weigh the raw materials by mass percentage: 15%-25% of rubber powder and the rest of the base asphalt;

[0074] (2) heating the base asphalt to 160° C.-170° C., adding rubber powder to the base asphalt heated to a fluid state, and pre-stirring for 20-30 minutes to obtain a mixture A;

[0075] (3) The mixture A is temperature controlled to 170-180° C., subjected to high-speed shearing for 20-40 min at a shear rate of 4000-6000 r / min, and then stirred for 10-12 h at a stirring rate of 1500-2000 r / min under temperature control to obtain a premix;

[0076] (4) Pretreatment of finely separated recycled materials: The recycled asphalt mixture (RAP) is subjected to dry fine separation treatment, and the finely separated recycled materials with a maximum particle size not exceeding 3 mm are sieved and dried at 60°C to a moisture content of ≤0.5%, and kept warm at 60°C.

[0077] (5) Weigh the raw materials by mass percentage: 65%-75% premix, 2%-4% polymer modifier, 0.5%-1.5% resin, 0.1%-0.5% stabilizer, and the total amount of stone powder and fine separation recycled material is 10%-32%.

[0078] (6) The premix is ​​temperature controlled to 175°C-185°C, and the weighed polymer modifier, resin, and fine separation recycled material are added at the same time, and stirred for 30-60 minutes at a stirring rate of 600-1000 r / min, followed by high-speed shearing for 20-40 minutes at a shear rate of 4500-5000 r / min, and stirring is continued for 2-4 hours to obtain a mixture B;

[0079] (7) Mixture B is kept at 175°C-185°C, stabilizer is added, and stirring is continued for 1-2 hours at a stirring rate of 600-1000 r / min to obtain mixture C. If stone powder is not added, mixture C is a high-temperature pavement joint sealant containing finely separated recycled materials;

[0080] (8) If stone powder needs to be added, keep the mixture C at 175℃-185℃, add stone powder, and continue stirring for 1-2 hours at a stirring rate of 600-1000r / min. After stopping stirring, a high-temperature pavement joint sealing adhesive containing finely separated recycled materials is obtained.

[0081] The present invention aims at the problems of complex process and unbalanced performance of conventional caulking glue, and at the same time considers the deep regeneration of old asphalt in finely separated recycled materials and the full shearing of old mineral materials, and proposes a caulking glue preparation process of first preparing rubber modified asphalt premix, then adding polymer modifier, tackifier, finely separated recycled materials for shearing and blending, and finally adding stabilizer. The process has significant advantages: first, various materials play a specific and synergistic role (rubber asphalt has high temperature and high rebound characteristics, polymer modifier improves low temperature performance, tackifier ensures viscosity and durability, stabilizer ensures stability and anti-aging, and The first is to start with the first step (interaction between various components such as asphalt, SBS, rubber powder, resin, etc.) to balance the comprehensive performance of the caulking adhesive and make it more environmentally adaptable; the second is to prepare the rubber modified asphalt premix in advance to reduce the preparation time of the later caulking adhesive. This prefabrication process allows the rubber powder and the matrix asphalt to fully blend with each other, thereby improving the uniformity and quality stability of the caulking adhesive; the third is to add finely separated recycled materials without increasing the extra preparation time, and can be mixed with polymer modifiers and thickeners for preparation, which not only ensures the simplification of the preparation process, but also balances the high temperature stability, elastic recovery and viscosity level of the caulking adhesive.

[0082] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.

[0083] Example 1

[0084] This embodiment provides a high-temperature pavement joint sealing adhesive, which includes the following components by mass percentage:

[0085] 70.8% premix, 2.5% T6302H SBS modifier, 0.7% C9 resin, 0.1% sulfur and 25.9% talc;

[0086] The premix includes the following components by mass percentage: 20% rubber powder and the rest is 70# heavy cross-linking matrix asphalt;

[0087] The particle size of the rubber powder is 60 mesh, the ash value is ≤18%, and the acetone extract is ≤20%; the talcum powder meets the following requirements: the passing rate of the 0.075mm sieve hole is 92%, and the passing rate of the 0.15mm sieve hole is 100%.

[0088] Example 2

[0089] This embodiment provides a high-temperature pavement sealant, which is different from Embodiment 1 in that the content of stone powder is changed, talcum powder is 28.6%, and premix is ​​68.1%, and the rest is consistent with Embodiment 1.

[0090] Example 3

[0091] This embodiment provides a high-temperature pavement sealant, which is different from Embodiment 1 in that the content of stone powder is changed, 31.0% talcum powder and 65.7% premix, and the rest is consistent with Embodiment 1.

[0092] Example 4

[0093] This embodiment provides a high-temperature pavement sealant, which differs from Embodiment 2 in that the content of the SBS modifier is changed, with 2.1% of T6302H type SBS modifier and 68.5% of premix, and the rest is consistent with Embodiment 2.

[0094] Example 5

[0095] This embodiment provides a high-temperature pavement caulking glue, which is different from Embodiment 2 in that the filler includes stone powder and finely separated recycled material, 14.3% talcum powder, 14.3% finely separated recycled material, and the rest is consistent with Embodiment 2.

[0096] Example 6

[0097] This embodiment provides a high-temperature pavement joint sealing adhesive, which is different from Embodiment 2 in that the filler includes finely separated recycled material, the finely separated recycled material accounts for 28.6%, and the rest is consistent with Embodiment 2.

[0098] Example 7

[0099] This embodiment provides a high-temperature pavement caulking adhesive, which differs from Embodiment 2 in that C9 resin is replaced by EVA, and the rest is consistent with Embodiment 2.

[0100] Example 8

[0101] This embodiment provides a high-temperature pavement joint sealing adhesive, which includes the following components by mass percentage:

[0102] 63.4% premix, 4% T6302H SBS modifier, 0.5% C9 resin, 0.1% sulfur, 16% talc and 16% finely separated recycled material;

[0103] The premix includes the following components by mass percentage: 15% rubber powder and the rest is 70# heavy cross-linking base asphalt;

[0104] The particle size of the rubber powder is 60 meshes, the ash value is ≤18%, and the acetone extract is ≤20%.

[0105] Example 9

[0106] This embodiment provides a high-temperature pavement joint sealing adhesive, which includes the following components by mass percentage:

[0107] 75.5% premix, 2% T6302H SBS modifier, 1.5% C9 resin, 0.5% sulfur, 10.25% talc and 10.25% finely separated recycled material;

[0108] The premix includes the following components by mass percentage: 25% rubber powder and the rest is 70# heavy cross-linking base asphalt;

[0109] The particle size of the rubber powder is 60 meshes, the ash value is ≤18%, and the acetone extract is ≤20%.

[0110] Examples 10-13

[0111] Embodiments 10-13 provide a method for preparing a high-temperature pavement crack sealing adhesive. Embodiments 10-13 weigh raw materials according to the component formula amounts in Embodiments 1-4, and specifically include the following steps:

[0112] (1) Weigh the raw materials according to the formulas in Examples 1-4 by mass percentage: including rubber powder and 70# heavy cross-linking base asphalt;

[0113] (2) heating the base asphalt to 170° C. and adding rubber powder to the base asphalt heated to a fluid state to obtain a mixture A;

[0114] (3) controlling the temperature to 175° C., performing high-speed shearing for 20 min at a shear rate of 4500 r / min, and then stirring for 12 h at a stirring rate of 1500 r / min under temperature control to obtain a premix;

[0115] (4) The raw materials were weighed in percentage by mass according to the formula amounts in Examples 1-4: premix, T6302H SBS modifier, C9 resin, sulfur and talcum powder.

[0116] (5) Controlling the temperature to 180°C, adding SBS and resin at the same time, stirring for 30 min at a stirring rate of 800 r / min, then high-speed shearing for 20 min at a shear rate of 4500 r / min, and continuing stirring for 2 h to obtain a mixture B;

[0117] (6) Control the temperature to 180°C, add sulfur, and continue stirring for 1 hour at a stirring rate of 800 r / min;

[0118] (7) Control the temperature to 180°C, add talcum powder, and continue stirring for 1 h at a stirring rate of 800 r / min;

[0119] (8) After stopping stirring, a high-temperature pavement caulking adhesive is obtained.

[0120] Embodiment 14

[0121] This embodiment provides a method for preparing a high-temperature pavement crack sealing adhesive, wherein the raw materials are weighed according to the component formula in Example 5, and specifically comprises the following steps:

[0122] (1) According to the formula in Example 5, weigh the raw materials by mass percentage: 20% of rubber powder and the rest of 70# heavy cross-linking base asphalt;

[0123] (2) heating the base asphalt to 170° C. and adding rubber powder to the base asphalt heated to a fluid state to obtain a mixture A;

[0124] (3) controlling the temperature to 175° C., performing high-speed shearing for 20 min at a shear rate of 4500 r / min, and then stirring for 12 h at a stirring rate of 1500 r / min under temperature control to obtain a premix;

[0125] (4) RAP is subjected to dry fine separation to prepare 0-2.36 mm oil-rich waste material, which is dried at 60°C until the moisture content is less than 0.5%;

[0126] (5) Weigh the raw materials by mass percentage: 68.1% premix, 2.5% T6302H SBS modifier, 0.7% C9 resin, 0.1% sulfur, 14.3% talc, and 14.3% finely separated recycled material.

[0127] (6) Controlling the temperature to 180° C., adding SBS, resin, and fine separation recycled material at the same time, stirring for 30 min at a stirring rate of 800 r / min, then high-speed shearing for 20 min at a shear rate of 4500 r / min, and continuing stirring for 2 h to obtain a mixture B;

[0128] (7) When the temperature is controlled to 180°C, sulfur is added and stirring is continued for 1 hour at a stirring rate of 800 r / min;

[0129] (8) When the temperature is controlled to 180° C., talcum powder is added and stirring is continued for 1 h at a stirring rate of 800 r / min. After stopping stirring, a high-temperature pavement joint sealing adhesive containing finely separated recycled materials is obtained.

[0130] Embodiment 15

[0131] This embodiment provides a method for preparing a high-temperature pavement sealant, which is different from Embodiment 14 in that the order of adding SBS, resin, and finely separated recycled materials is adjusted;

[0132] In step (6), the temperature is controlled to 180° C., SBS and resin are added, stirred for 30 min at a stirring rate of 800 r / min, then high-speed shearing is performed for 10 min at a shear rate of 4500 r / min, then fine separation recycled material is added and stirred for 30 min at a stirring rate of 800 r / min, high-speed shearing is performed for 10 min at a shear rate of 4500 r / min, and stirring is continued for 2 h to obtain a mixture B;

[0133] The remaining steps are consistent with Example 14.

[0134] Example 16

[0135] This embodiment provides a method for preparing a high-temperature pavement sealant, which is different from Embodiment 14 in that the order of adding SBS, resin, and finely separated recycled materials is adjusted;

[0136] Wherein in step (6), the temperature is controlled to 180° C., the finely separated recycled material is added, stirred for 30 min at a stirring rate of 800 r / min, then high-speed shearing is performed for 10 min at a shear rate of 4500 r / min, then SBS and resin are added and stirred for 30 min at a stirring rate of 800 r / min, high-speed shearing is performed for 10 min at a shear rate of 4500 r / min, and stirring is continued for 2 h to obtain a mixture B;

[0137] The remaining steps are consistent with Example 14.

[0138] Embodiment 17

[0139] This embodiment provides a method for preparing a high-temperature pavement crack sealing adhesive, wherein the raw materials are weighed according to the component formula in Example 6, and specifically comprises the following steps:

[0140] (1) According to the formula in Example 6, weigh the raw materials by mass percentage: 20% of rubber powder and the rest of 70# heavy cross-linking base asphalt;

[0141] (2) heating the base asphalt to 170° C. and adding rubber powder to the base asphalt heated to a fluid state to obtain a mixture A;

[0142] (3) controlling the temperature to 175° C., performing high-speed shearing for 20 min at a shear rate of 4500 r / min, and then stirring for 12 h at a stirring rate of 1500 r / min under temperature control to obtain a premix;

[0143] (4) RAP is subjected to dry fine separation to prepare 0-2.36 mm oil-rich waste material, which is dried at 60°C until the moisture content is less than 0.5%;

[0144] (5) Weigh the raw materials by mass percentage: 68.1% premix, 2.5% T6302H SBS modifier, 0.7% C9 resin, 0.1% sulfur, and 28.6% fine separation recycled material;

[0145] (6) Controlling the temperature to 180° C., adding SBS, resin, and fine separation recycled material at the same time, stirring for 30 min at a stirring rate of 800 r / min, then high-speed shearing for 20 min at a shear rate of 4500 r / min, and continuing stirring for 2 h to obtain a mixture B;

[0146] (7) When the temperature is controlled to 180°C, sulfur is added and stirring is continued for 1 hour at a stirring rate of 800 r / min;

[0147] (8) After stopping stirring, a high-temperature pavement caulking adhesive containing finely separated recycled materials is obtained.

[0148] Embodiment 18

[0149] This embodiment provides a method for preparing a high-temperature pavement sealant. The raw materials are weighed according to the component formula in Example 7, and the preparation method is consistent with Example 11.

[0150] Embodiment 19

[0151] This embodiment provides a method for preparing a high-temperature pavement crack sealing adhesive, wherein the raw materials are weighed according to the component formula in Example 8, and specifically comprises the following steps:

[0152] (1) According to the formula in Example 8, weigh the raw materials by mass percentage: 15% rubber powder and the rest 70# heavy cross-linking base asphalt;

[0153] (2) heating the base asphalt to 160° C. and adding rubber powder to the base asphalt heated to a fluid state to obtain a mixture A;

[0154] (3) controlling the temperature to 180° C., performing high-speed shearing for 40 min at a shear rate of 4000 r / min, and then stirring for 10 h at a stirring rate of 2000 r / min under temperature control to obtain a premix;

[0155] (4) RAP is subjected to dry fine separation to prepare 0-2.36 mm oil-rich waste material, which is dried at 60°C until the moisture content is less than 0.5%;

[0156] (5) Weigh the raw materials by mass percentage: 65% premix, 4% T6302H SBS modifier, 1% C9 resin, 0.1% sulfur, 14.95% talc and 14.95% fine separation recycled material;

[0157] (6) Controlling the temperature to 175° C., adding SBS, resin, and fine separation recycled material, stirring for 60 min at a stirring rate of 600 r / min, then high-speed shearing for 40 min at a shear rate of 5000 r / min, and continuing stirring for 4 h to obtain a mixture B;

[0158] (7) When the temperature is controlled to 175°C, sulfur is added and stirring is continued for 2 h at a stirring rate of 600 r / min;

[0159] (8) When the temperature is controlled to 175°C, talcum powder is added and stirring is continued for 2 h at a stirring rate of 600 r / min. After stopping stirring, a high-temperature pavement joint sealing adhesive containing finely separated recycled materials is obtained.

[0160] Embodiment 20

[0161] This embodiment provides a method for preparing a high-temperature pavement crack sealing adhesive, wherein the raw materials are weighed according to the component formula in Example 9, and specifically comprises the following steps:

[0162] (1) According to the formula in Example 9, weigh the raw materials by mass percentage: 25% rubber powder and the rest 70# heavy cross-linking base asphalt;

[0163] (2) heating the base asphalt to 165° C. and adding rubber powder to the base asphalt heated to a fluid state to obtain a mixture A;

[0164] (3) controlling the temperature to 175° C., performing high-speed shearing for 30 min at a shear rate of 6000 r / min, and then stirring for 11 h at a stirring rate of 1750 r / min under temperature control to obtain a premix;

[0165] (4) RAP is subjected to dry fine separation to prepare 0-2.36 mm oil-rich waste material, which is dried at 60°C until the moisture content is less than 0.5%;

[0166] (5) Weigh the raw materials by mass percentage: 75% premix, 2% T6302H SBS modifier, 2% C9 resin, 0.5% sulfur, 10.25% talc and 10.25% fine separation recycled material;

[0167] (6) Controlling the temperature to 185° C., adding SBS, resin, and fine separation recycled material, stirring for 45 min at a stirring rate of 1000 r / min, then high-speed shearing for 30 min at a shear rate of 4750 r / min, and continuing stirring for 3 h to obtain a mixture B;

[0168] (7) While controlling the temperature to 185°C, add sulfur and continue stirring for 1.5 hours at a stirring rate of 1000 r / min;

[0169] (8) When the temperature is controlled to 185°C, talcum powder is added and stirring is continued for 1.5 hours at a stirring rate of 1000 r / min. After stopping stirring, a high-temperature pavement joint sealing adhesive containing finely separated recycled materials is obtained.

[0170] Comparative Example 1

[0171] This comparative example provides a method for preparing a high-temperature pavement crack sealing adhesive, which is different from Example 11 in that no rubber asphalt premix material is prepared, and specifically comprises the following steps:

[0172] (1) Weigh the raw materials by mass percentage: 20% rubber powder and the rest 70# heavy cross-linking base asphalt;

[0173] (2) Weigh the raw materials by mass percentage: the total amount of rubber powder and base asphalt is 68.1%, T6302H SBS modifier is 2.5%, C9 resin is 0.7%, sulfur is 0.1%, and talc is 28.6%;

[0174] (3) Control the temperature to 180°C, add rubber powder, SBS and resin to the base asphalt at the same time, stir for 30 min at a stirring rate of 800 r / min, then perform high-speed shearing for 20 min at a shear rate of 4500 r / min, and continue stirring for 2 h;

[0175] (4) Under temperature control, add sulfur and continue stirring for 1 hour at a stirring rate of 800 r / min;

[0176] (5) Under temperature control, add talcum powder and continue stirring for 1 h at a stirring rate of 800 r / min;

[0177] (6) After stopping stirring, a high-temperature pavement caulking adhesive is obtained.

[0178] Comparative Example 2

[0179] This comparative example provides a method for preparing a high-temperature pavement sealant, which differs from Example 17 in that the raw material components of Comparative Example 2 do not contain an SBS modifier, namely (5) the raw materials are weighed by mass percentage: 70.6% premix, 0.7% C9 resin, 0.1% sulfur, and 28.6% finely separated recycled material. The preparation method is consistent with Example 17.

[0180] Test samples: The high-temperature pavement sealant prepared in Examples 10-20 and the high-temperature pavement sealant prepared in Comparative Examples 1-2 were used as test samples.

[0181] Test Method

[0182] The test method is as shown in Table 1 below.

[0183] Table 1

[0184] Test items Test Method Softening point(℃) JTG E20 T 0606 Cone penetration (25℃, 0.1mm) JT / T 740-2015 Elastic recovery rate (%) JT / T 740-2015 Low temperature stretching JT / T 740-2015 Brookfield viscosity (Pa·s) JTG E20 T 0625

[0185] Test Example 1

[0186] The same finely separated recycled material is used in the above embodiments, whose old asphalt content is 7.8%, the old asphalt penetration (100 g, 25° C., 5 s) is 29 (0.1 mm), and the particle size distribution of the old mineral material is shown in Table 2.

[0187] Table 2

[0188]

[0189] Test samples: the caulking glue provided in Example 11 and Comparative Example 1, the test results are shown in Table 3.

[0190] Table 3

[0191]

[0192] It can be seen from Table 3 that the softening point, cone penetration, elastic recovery rate and other indicators of Comparative Example 1 are inferior to those of Example 11. It can be seen that the method of pre-preparing the rubber asphalt premixed material proposed in the embodiment of the present invention, that is, using long-term and reasonable process shearing and stirring, is conducive to the full swelling and degradation of the rubber powder, and uniform dispersion in the asphalt phase, thereby ensuring that the caulking glue has good high temperature stability and ductility.

[0193] Test Example 2

[0194] Test sample: the caulking glue provided in Example 11 and Example 18.

[0195] Table 4

[0196]

[0197] It can be seen from the data in Table 4 that the performance of the caulking adhesive can meet the requirements whether the resin is C9 resin or EVA. Compared with the two, the overall performance indicators of the caulking adhesive using EVA are better, and the Brookfield viscosity is lower.

[0198] Test Example 3

[0199] Test sample: the caulking glue provided in Example 10, Example 11 and Example 12.

[0200] Table 5

[0201]

[0202] From the data in Table 5, it can be seen that an appropriate amount of stone powder can reduce the friction inside the cementitious material, improve the fluidity of the caulking glue, make it easier to fill the cracks in the pavement, and improve the construction efficiency. However, too much stone powder will also reduce the strength of the caulking glue and increase the porosity. When the amount of SBS modifier added is consistent with the amount of resin, the softening point of the caulking glue increases with the increase of stone powder content. When the stone powder content exceeds 28.6%, the softening point decreases slightly. When the stone powder content is 28.6%, the elastic recovery rate of the caulking glue reaches the maximum.

[0203] Test Example 4

[0204] Test sample: the caulking glue provided in Example 11 and Example 13.

[0205] Table 6

[0206]

[0207] It can be seen from the data in Table 6 that, when the stone powder content and resin remain unchanged, increasing the amount of SBS modifier added is conducive to improving the softening point, but too high an SBS modifier content will increase the cost of the caulking adhesive. When the SBS content is 2.1% to 2.5%, it has met the requirements of the JT / T 740-2015 technical standard.

[0208] Test Example 5

[0209] Test sample: the caulking glue provided in Example 14, Example 15, and Example 16.

[0210] Table 7

[0211]

[0212] As shown in Table 7, different processes have an impact on the performance indicators of the caulking glue, and the order of adding the finely separated recycled materials has a great impact on the performance of the caulking glue. When SBS, resin, and finely separated recycled materials are added simultaneously (Example 14), its performance index is optimal. In addition, when Example 15 and Example 16 are compared, it can be found that the caulking glue prepared by the finely separated recycled materials is preferentially added, and its softening point, cone penetration, and elastic recovery are all improved, and the viscosity is reduced and is conducive to construction, which is caused by the different lengths of the finely separated recycled materials adding time, the longer the stirring time of the finely separated recycled materials, the better the miscibility of the old asphalt and the matrix asphalt, the more sufficient the shearing of the old mineral material, and the better the performance of the caulking glue.

[0213] Test Example 6

[0214] Test samples: Comparative Examples 1-2, and the caulking adhesives provided in Examples 11, 14, 17, and 19-20. The test results are shown in the table below.

[0215] Table 8

[0216]

[0217] As can be seen from the test data in the table above, Examples 11, 14, 17, and 19-20 can all meet the requirements of "Pavement Heating Sealant" (JT / T 740-2015). The high-temperature pavement sealant containing finely separated recycled materials provided by the present invention has good high-temperature performance, deformation characteristics, and bonding ability, and all indicators are better than the sealant indicators prepared by stone powder in Comparative Example 1. At the same time, it can be found from the analysis of Examples 11, 14, and 17 that all indicators of Examples 14 and 17 are better than those of Example 11. After adding finely separated recycled materials, the softening point is increased by more than 4°C, which improves the high-temperature performance of the sealant, and the elastic recovery rate is increased by more than 14%, which improves the deformation characteristics of the sealant. At the same time, the viscosity is reduced, thereby improving the construction and workability. It is found from the analysis of Examples 11, 14, and 17 that with the increase in the content of finely separated recycled materials, the softening point and elastic recovery rate of the sealant are improved, and the viscosity is reduced, which is conducive to on-site construction. Example 17 has better comprehensive performance and a high dosage of finely separated recycled materials. It simultaneously processes two major solid wastes, namely, waste tires and finely separated recycled materials. It is environmentally friendly and has considerable economic benefits. The reason is that after adding finely separated recycled materials and dissolving them in rubber asphalt, under the action of high temperature and shear, the large micelles of asphalt will be broken, exposing many active points. These active points combine with small molecules in asphalt to form semi-polymerization, which can form new asphalt colloids and then form a spatial network structure, thereby achieving the effect of improving the performance of the caulking glue.

[0218] In addition, in Example 11, Example 14, and Example 17, the content of old asphalt in the finely separated recycled material is 7.8%. Replacing part of the base asphalt with the aged asphalt in the finely separated recycled material can reduce the amount of base asphalt used and reduce costs.

[0219] It can be seen from the data in the table that compared with Comparative Example 17, Comparative Example 2 lacks the synergistic effect of the SBS modifier and other components, the performance of various indicators of the caulking glue is reduced, and the overall performance is reduced.

[0220] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A high temperature pavement sealant, characterized in that: It includes the following components: premix, polymer modifier, tackifier, stabilizer and filler; Wherein, the premix includes rubber powder and base asphalt.

2. The high temperature pavement sealant according to claim 1, characterized in that: The high-temperature pavement sealant comprises the following components by mass percentage: 65%-75% premix, 2%-4% polymer modifier, 0.5%-1.5% tackifier, 0.1%-0.5% stabilizer and 10%-32% filler; The premix comprises the following components by mass percentage: 15%-25% rubber powder and 75%-85% base asphalt.

3. The high temperature pavement sealant according to claim 1, characterized in that: The base asphalt includes 70# heavy cross-linked base asphalt; The particle size of the rubber powder is 60-100 meshes, the ash value of the rubber powder is ≤18%, and the acetone extract content of the rubber powder is ≤20%.

4. The high temperature pavement sealant according to claim 1, characterized in that: The filler includes at least one of finely separated recycled material and stone powder; Preferably, the stone powder includes at least one of mineral powder and talcum powder; Preferably, the particle size of the finely separated recycled material is ≤3 mm, the moisture content of the finely separated recycled material is ≤0.5%, the old asphalt content of the finely separated recycled material is 6%-8%, and the needle penetration of the old asphalt is ≥20 (0.1 mm); Preferably, the particle size of the stone powder is ≤0.15 mm.

5. The high temperature pavement sealant according to claim 1, characterized in that: The polymer modifier includes at least one of linear T6302H type, T161 type and T171 type styrene-butadiene-styrene block copolymers.

6. The high temperature pavement sealant according to claim 1, characterized in that: The tackifier includes at least one of C9 resin, C5 resin and EVA.

7. The high temperature pavement sealant according to claim 1, characterized in that: The stabilizer includes sulfur.

8. The method for preparing the high temperature pavement sealant according to any one of claims 1 to 7, characterized in that: The following steps are involved: The rubber powder and the base asphalt are mixed according to the formula amount to obtain a premix; The premix, polymer modifier, tackifier, stabilizer and filler are mixed according to the formula amount to obtain the high-temperature pavement crack sealing glue.

9. The method for preparing the high temperature pavement sealant according to claim 8, characterized in that: The process of mixing the rubber powder and base asphalt includes: heating the base asphalt to 160°C-170°C, adding the rubber powder, stirring for 20-30 minutes to obtain a mixture A, controlling the temperature of the mixture A to 170-180°C, shearing for 20-40 minutes at a shear rate of 4000-6000 r / min, and then stirring for 10-12 hours at a stirring rate of 1500-2000 r / min to obtain a premix.

10. The method for preparing the high temperature pavement sealant according to claim 8, characterized in that: The pretreatment process of finely separated recycled materials includes: subjecting the asphalt mixture recycled materials to dry fine separation treatment, and screening to obtain finely separated recycled materials; The process of mixing the premix, polymer modifier, tackifier, stabilizer and filler comprises: controlling the temperature of the premix to 175°C-185°C, adding the polymer modifier, tackifier and fine separation recycled material, stirring for 30-60 minutes at a stirring rate of 600-1000 r / min, then shearing for 20-40 minutes at a shear rate of 4500-5000 r / min, then stirring for 2-4 hours to obtain a mixture B, maintaining the temperature of the mixture B at 175°C-185°C, adding the stabilizer, stirring for 1-2 hours at a stirring rate of 600-1000 r / min to obtain a mixture C, and when the filler also includes stone powder, maintaining the temperature of the mixture C at 175°C-185°C, adding other fillers, and then stirring for 1-2 hours at a stirring rate of 600-1000 r / min.

Citation Information

Patent Citations

  • Asphalt pavement crack filling adhesive and preparation method thereof

    CN103571212A

  • A potting compound, its preparation method and application

    CN111534277B

  • Road seam filling asphalt material, and preparation method and applications thereof

    CN105131618A

  • Waste rubber powder modified asphalt and preparation method thereof

    CN107778888A

Cited By

  • Road surface crack pouring material based on ST-BA copolymer modifier and preparation method

    CN120082220A